Influence of the powder/liquid ratio and storage time of conventional glass ionomer cements in diametral tensile strength - Tamiris Carolina da Silva; Camila Rodrigues dos Santos; Rodrigo Borges Fonseca; Terezinha Jesus Esteves Barata (Revista Sul-Brasileira de Odontologia, 2015)
The Glass Ionomer Cements (GICs) are the most versatile dental material with extensive clinical indication. However, the mechanical strength of conventional GICs (C-GICs) is still unsatisfactory under areas of masticatory forces. Objective: To evaluate the influence of C-GIC proportioning system (powderliquid and encapsulated) and storage period (1h, 24h and 7 days) on Diametral Tensile Strength (DTS). Material and methods: The two variables were tested in relation to C-GIC (Riva Self Cure, SDI, Australia). The following proportioning systems were tested: powder-liquid by weight (g:g) and powder-liquid by volume (flat scoop: drop) and encapsulated system (pre-dosed capsules). Five C-GIC specimens were prepared, according to ISO specification #9917 for each variable to be studied. The specimens were stored in plastic containers containing distilled water and kept at 37ºC and 100% humidity until the mechanical testing in a universal testing machine (Instron Corp., USA) at a speed 0.5 mm/min. The data were submitted to two-way ANOVA and Tukey test for multiple comparisons (α = 0.05). Results: The proportioning system (P < 0.0001) and storage time (P < 0.0001) were significant predictors of DTS, however with no interaction between these factors. Conclusion: The DTS of C-GICs was influenced by storage time (1 hour < 24 hours < 7 days) and by the proportioning system only for the initial period of its setting reaction.